Efavirenz modulation of sleep spindles and sleep spectral profile. (12th August 2014) - Simen, Arthur A.; Ma, Junshui; Svetnik, Vladimir; Mayleben, David; Maynard, James; Roth, Adam; Mixson, Lori; Mogg, Robin; Shera, David; George, Laura; Mast, T. Chris; Beals, Chan; et al.
Summary Non‐nucleoside reverse transcriptase inhibitors are important antiretroviral agents for the treatment of human immunodeficiency virus. Some non‐nucleoside reverse transcriptase inhibitors, in particular efavirenz, have prominent effects on sleep, cognition and psychiatric variables that limit their tolerability. To avoid confounds due to drug–drug and drug–disease interactions, we assessed the effects of efavirenz in healthy volunteers on sleep, cognition and psychological endpoints during the first week of treatment. Forty healthy male subjects were randomized to receive placebo or efavirenz 600 mg nightly for 7 days after completion of a 3‐day placebo run‐in period. Treatment with efavirenz was associated with reduced time to sleep onset in the Maintenance of Wakefulness Test, an increase in non‐rapid eye movement sleep, a large exposure‐related decrease in sigma band spectral density and sleep spindle density during non‐rapid eye movement sleep, and reduced performance on an attention switching task. Because efavirenz has been shown to have serotonin 2A receptor partial‐agonist properties, we reasoned that antagonism of serotonin 2A receptor signalling in the thalamic reticular nucleus, which generates sleep spindles and promotes attention, may be responsible. Consistent with predictions, treatment of healthy volunteers with a single dose of a serotonin 2A receptor antagonist was found to significantly suppress sigma band spectral density in an exposure‐related manner and modulated the overall spectral profile in a manner highly similar to that observed with efavirenz, consistent with the notion that efavirenz exhibits serotonin 2A receptor partial‐agonist pharmacology in humans.